Efficient use of side information in multiple-antenna data transmission over fading channels. - Narula, A.
We derive performance limits for two closely related communication scenarios involving a wireless system with multiple-element transmitter antenna arrays: a point-to-point system with partial side information at the transmitter, and a broadcast system with multiple receivers. In both cases, ideal beamforming is impossible, leading to an inherently lower achievable performance as the quality of the side information degrades or as the number of receivers increases. Expected signal-to-noise ratio (SNR) and mutual information are both considered as performance measures. In the point-to-point case, we determine when the transmission strategy should use some form of beamforming and when it should not. We also show that, when properly chosen, even a small amount of side information can be quite valuable. For the broadcast scenario with an SNR criterion, we find the efficient frontier of operating points and show that even when the number of receivers is larger than the number of antenna array elements, significant performance improvements can be obtained by tailoring the transmission strategy to the realized channel
Keywords: SNR; Beamforming; Broadcast system; Fading channels; Multiple-antenna data transmission; Multiple-element transmitter antenna arrays; Partial side information; Performance limits; Performance measures; Point-to-point system; Signal-to-noise ratio; Wireless system